Air pollution at parking‐lots of Vilnius - Baltrenas, Pranas; Kaziukoniene, Danguole; Kvasauskas, Mindaugas (Journal of Environmental Engineering and Landscape Management, 2004)
The expansion of Vilnius creates the need for the installation of new parking facilities. This problem could be solved by establishing guarded parking‐lots or modern underground and multi‐storey garages, in order to economize useful land and comply with the requirements of environmentalists. Investigation was carried out on parking‐lots of Vilnius. All the guarded parking‐lots are divided into three types in accordance with the size of the lot and the type of vehicles parked on it. Measurements were carried out at a lot of each type. The concentrations of hydrocarbons, nitric oxide, carbon monoxide and dust were measured. Guarded parking‐lots located at the crossroad of Ateities and L. Giros streets, on Architektu and Č. Sugiharos streets were selected for the investigation. The parking‐lot located at the crossroad of Ateities and L. Giros streets had the highest concentration of nitric oxide overrunning the permitted concentration up to 1,9 times. Besides, the concentration of carbon monoxide and hydrocarbons also overran the permitted norms. The lowest concentrations were found after measuring dust concentration in the air. Oro tarša Vilniaus automobilių stovėjimo aikštelėse Santrauka. Vilniui plečiantis, kyla vis didesnis naujų automobilių parkavimo vietų poreikis. Šiai problemai spręsti gali būti įrengtos saugomos automobiliu aikštelės arba, siekiant kuo mažesnių naudingos žemės sąnaudų ir laikantis gamtosauginių reikalavimų, požeminiai ar kelių aukštų šiuolaikiniai garažai. Tyrimai buvo atliekami Vilniaus automobilių stovėjimo aikštelėse. Visos saugomos automobilių stovėjimo aikštelės suskirstytos į tipus pagal jose laikomo transporto tipą ir aikštelių dydį. Matavimams pasirinkta po vieną kiekvieno tipo aikštelę. Nustatyta angliavandenilių, azoto oksido, anglies monoksido ir dulkių koncentracijos. Tyrimams pasirinktos saugomos automobiliu stovėjimo aikštelės prie Ateities ir L. Giros gatvių sankryžos, Architektu bei Č. Sugiharos gatvėse. Ateities ir L. Giros gatvių sankryžoje esančioje aikštelėje didžiausios azoto oksido koncentracijos (leistinąsias viršija iki 1,9 karto). Leistinąsias koncentracijas viršija ir anglies monoksidas bei angliavandeniliai. Mažiausios reikšmės nustatytos išmatavus dulkių koncentracijas atmosferos ore. Reikšminiai žodžiai: oro tarša, mobilieji taršos šaltiniai, anglies monoksidas, azoto oksidas, angliavandeniliai, dulkės. First Published Online: 14 Oct 2010